BILANGAN RADIO PADA GRAF SIKEL DENGAN DAN GRAF SIKEL TENGAH - Meivita Nur Arifiani; R. Heru Tjahyana (MATEMATIKA FSM, UNDIP, 2014)
ABSTRACT.Let be a simple connected graph and denote the distance between any two vertices in . The maximum distance between any pair of vertices is called the diameter denoted by . A radio labeling for is an injectif function such that for any vertices dan it is satisfied that . The span of an radio labeling is max . The minimum span of a radio labeling of is called radio number denoted by . In this Thesis we study radio number of cycle with and graph of cycle .